Enhancing rural drinking water safety using an Mg–Al-type layered double hydroxide foil as a new point-of-use disinfection tool - Taufiq Ihsan; Erni Johan; Satoru Fukugaichi; Naoto Matsue (Journal of Water, Sanitation and Hygiene for Development, 2023)
Point-of-use (POU) drinking water treatment is crucial for residents in resource-constrained areas. This study introduces a layered double hydroxide (LDH) foil, an innovative POU device that eliminates waterborne pathogens via adsorption. It is an aluminum foil coated with magnesium–aluminum (Mg–Al)-type LDH, a recognized human-safe pathogen adsorbent. Its sheet-like morphology enables easy retrieval of inherently powdered LDH from post-disinfected water. Coating with Mg–Al LDH foils was accomplished by immersing aluminum foils in alkaline magnesium solutions, resulting in the on-surface formation of LDH. Using 12 distinct alkaline magnesium solutions, 12 types of LDH foils were prepared. Most LDH foils demonstrated >99% removal of Escherichia coli (DH5α strain) within 3–24 h when 100 mL of water was inoculated with DH5α at approximately 103 colony-forming units (CFU)/mL agitated with a 25-cm2 LDH foil piece. The LDH foil with the highest efficacy had a maximum adsorption capacity of approximately 1.3 × 106 CFU per 1-cm2 LDH foil. Furthermore, the LDH foil was regenerated by submersing it in the alkaline solution during its preparation, enabling multiple reuses. Owing to its straightforward production and application, the LDH foil holds substantial promise as a convenient-to-use adsorbent for batch water disinfection, such as jug water, in rural households. HIGHLIGHTS LDH foils, composed of aluminum foil coated with an Mg–Al-type LDH, function as a pathogen adsorbent.; Preparation involves a single step using various Mg sources and alkaline reagents.; Adding, removing, and regenerating LDH foils are all simple processes.; Validation tests with actual water samples are essential to confirm its effectiveness.;